Keramikken og ovnen fra Barmer samt brændingsforløbet - Barlebo, Rikke (Hikuin, 2001)
The pottery and kiln from Barmer and the result of the firing By Rikke Barlebo In 1984 the remains of two medieval pottery kilns were found at Barmer, southwest of Aalborg. On the basis of the knowledge revealed by the archaeological excavation in 1985 and results from other European finds of medieval pottery kilns, a reconstruction of the Barmer kiln was made in the spring of 1987 at the Prehistoric Museum, Moesgaard, in Aarhus. The kiln was filled with a number of pots that were reconstructions of the pots excavated at Barmer. The result of the firing was successful, though a few details had to be adjusted to achieve a kiln which would work to full satisfaction. Barmer kiln II was built in the Spring of 1989 at Poulstrup, south of Aalborg, giving us a chance to make the necessary adjustments. The firing of Barmerkiln II was very successful, and indicated that with this construction of the kiln, we had come very close to the kiln used by the medieval potter at Barmer.